Optical properties and chemical behavior of Laser-dye Coumarin-500 and the influence of atmospheric corona discharges - KESKİN, SIDDIK SİNAN (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
Structure elucidation of Coumarin-500 Laser-dye in cyclohexane at room temperature has been studied by UV-Vis, Raman, and FTIR spectroscopic techniques. Optical properties and chemical behavior under the influence of atmospheric positive electric pulsed corona discharges were also examined. The effects of UV-Vis irradiation changed some optical parameters, such as decrease in optical density on the absorption spectrum and formation of photoproducts, due to the chromaticity removal. No significant optical changes were observed in the light absorption upon UV-irradiation but large changes in absorption spectrum were observed after positive electric corona discharge treatments. FTIR and Raman spectra in non-polar solvent are recorded and interpreted. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Coumarin-500; Laser-dye; UV-Vis spectrum; Raman scattering; FTIR spectrum; Plasma discharge treatment; GAIN CHARACTERISTICS; FLUORESCENCE; INTENSITY; MOLECULES; EMISSION; STATE